2015
DOI: 10.4314/ahs.v15i3.22
|View full text |Cite
|
Sign up to set email alerts
|

New pneumococcal conjugate vaccine introductions in four sub-Saharan African countries: a cross-country analysis of health systems’ impacts

Abstract: Background: Pneumonia is a main cause of under-five mortality in low-income settings. The pneumococcal conjugate vaccine (PCV) has been introduced in many countries as a tool in the disease's prevention. Although PCV's effectiveness has been established, less is known about the effects of introducing additional injectable vaccines into routine immunisation programmes, particularly in the context of resource-constrained settings. Objectives: To explore the effects of PCV introduction on the immunisation program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For example, in The Gambia, infant vaccination has reduced vaccine-type pneumococcal carriage not only among vaccinated children but also among non-vaccinated older children and adults, indicating a substantial herd effect [ 3 ]. However, not all countries have introduced vaccination of infants as implementation is limited by the high cost of the vaccine [ 4 ]. The cost of one dose of pneumococcal conjugate vaccine (PCV) can be very high in developed countries (> $100) [ 5 ].…”
Section: Main Textmentioning
confidence: 99%
“…For example, in The Gambia, infant vaccination has reduced vaccine-type pneumococcal carriage not only among vaccinated children but also among non-vaccinated older children and adults, indicating a substantial herd effect [ 3 ]. However, not all countries have introduced vaccination of infants as implementation is limited by the high cost of the vaccine [ 4 ]. The cost of one dose of pneumococcal conjugate vaccine (PCV) can be very high in developed countries (> $100) [ 5 ].…”
Section: Main Textmentioning
confidence: 99%
“…pneumoniae (the pneumococcus) is a major bacterial pathogen causing respiratory tract infections, with 515,000 deaths among children globally in 2015 [ 9 ]. The morbidity and mortality related to pneumonia of children under-five in Ethiopia is still high [ 10 , 11 ], despite the introduction of 13-valent pneumococcal conjugate vaccine (PCV13) in the infant immunisation program in 2011 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,9 By contrast, other studies have found that the adoption of new vaccines was perceived as an opportunity to retrain and strengthen healthcare workforce capacity and to further promote the benefit of immunization services as a whole, leveraging the availability of additional government resources or donor funding. [10][11][12] Further, social mobilization, outreach, and information campaigns that often accompany the launch of new vaccines may promote higher uptake and timeliness of other vaccines recommended for routine use in communities, specifically because new vaccines are recommended for concomitant administration with other traditional vaccines at established age intervals for vaccination programs. 13 Kenya has made immunizations a health priority, introducing new vaccines ahead of many other LMICs in sub-Saharan Africa, such as pneumococcal conjugate vaccine (PCV) in 2011 and rotavirus vaccine (RV) in 2014.…”
Section: Introductionmentioning
confidence: 99%